2013
DOI: 10.1088/1752-7155/7/2/026006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of drugs of abuse in exhaled breath using a device for rapid collection: comparison with plasma, urine and self-reporting in 47 drug users

Abstract: Exhaled breath has recently been identified as a matrix for the detection of drugs of abuse. This work aims to further document this application using a new and simple collection device in patients following recovery from acute intoxication. Breath, plasma and urine samples were collected from 47 patients (38 males, age range 25-74) together with interview data. Analysis of breath and plasma samples was done by liquid chromatography-mass spectrometry methods. Urine was screened using immunochemical reagents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 25 publications
5
97
0
3
Order By: Relevance
“…Drugs of abuse are also transported from the body in the PEx fraction (12,13 ). The work with drug testing has resulted in the development of a simple and disposable sampling device based on the use of a microparticle filter (13 ).…”
Section: Exhaled Breath Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs of abuse are also transported from the body in the PEx fraction (12,13 ). The work with drug testing has resulted in the development of a simple and disposable sampling device based on the use of a microparticle filter (13 ).…”
Section: Exhaled Breath Particlesmentioning
confidence: 99%
“…They have a large capacity and are used for cleaning of indoor air (20 ) and also as exhaust filters in respirator systems. A commercial sampling device based on this technology was used in a clinical study of illicit drug users recovering from acute intoxication (13 ). The results demonstrated that all 12 studied drug substances (Table 1) were detected in the collected exhaled breath sample at the time they were clinically recovered, which was estimated to be 12-24 h after drug intake.…”
Section: Potential Biomarkers Toxicologymentioning
confidence: 99%
“…When mass spectrometric assays give unexpectedly low results, one should contemplate the possibility of the presence of variants and scan for them. One reason for doing this is that a "missed" pathogenic variant would give the clinically correct result for the wrong reason, which might result in a failed opportunity for definitive genetic family testing (4,5 ). The other reason is that several of the variants are either nonpathogenic or of uncertain significance, leading to a potentially falsely low IGF-1 result being reported.…”
mentioning
confidence: 99%
“…Breath testing has also been successfully explored as an alternative method for drugs of abuse, since low molecular weight substances circulating in the body are to some extent exhaled in breath as part of aerosol particles (3 ). A variety of abused substances, including amphetamines, benzodiazepines, cannabis, cocaine, and opiates, are detectable in breath samples (4,5 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation